PENGUATAN KAPASITAS UMKM BIDANG SNACK DAN MAKANAN KHAS JAWA - Ariwibowo, Didik (Jurnal Pengabdian Vokasi, 2023)
[Strengthening MSME Capacity in The Field of Javanese Snacks and Foods] This paper studied about application of steam cooker technology. The teachnology apllied at a Small Manufacturer of wheat flour based snacks and foods industry to increase its productivity. The activities include: (i) designing and manufacturing of steam cooker, and (ii) techno-economy analysis. Fungsional and commercial capacity test were done to the equipments. The test results that the steam cooker has satisfied to proceed snacks and food as per design capacity. The steam cooker was able to cook dough to be various snakcs and foods. By the cooker production capacity increased to 30%..